Web-Based Tourism Decision Support Information System - Montree Kumngern (CV. AFDIFAL MAJU BERKAH, 2022)
Tourism is one of the potential resources that can be developed by each region. As one of the resources that generate foreign exchange for the country, this requires optimization in the provision of services to further support the potential of tourist areas to be visited. When this study was conducted, tourism in bangkok has used internet media in promotion. However, the system used is still not perfect. This problem comes from poor tourism data management and still not maximal some facilities in the running system. With some of these problems, it is time for the old system to be fixed. Not only to improve it, the author suggested to create some new features such as Simulation features and Decision Support features. In this study, the research method used is descriptive and action research, while the system approach used is structured with the method of system development using waterfall model. The tools used are context Diagram, data Flow Diagram (DFD), Data Dictionary, and Entity Relationship Diagram (ERD). Database design tools in the development of this information system is the normalization and table relation. The programming language used is PHP, with Adobe Dreamwaver CS5 tools. For the database, This Information System uses MySQL and for decision making, this information system uses the AHP (Analitycal Hierarchy Process) method with the creation of this information system, the author hopes that the information system that the author makes in the future can improve the quality of service for tourists and can help top tourism management in Bangkok to make decisions.